2013
DOI: 10.1002/jgrd.50128
|View full text |Cite
|
Sign up to set email alerts
|

Two years of atmospheric boundary layer observations on a 45‐m tower at Dome C on the Antarctic plateau

Abstract: [1] The lower atmospheric boundary layer at Dome C on the Antarctic plateau has been continuously monitored along a 45-m tower since 2009. Two years of observations (2009 and 2010) are presented. A strong diurnal cycle is observed near the surface in summer but almost disappears at the top of the tower, indicating that the summer nocturnal inversion is very shallow. Very steep inversions reaching almost 1 C m À1 on average along the tower are observed in winter. They are stronger and more frequent during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
123
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 85 publications
(132 citation statements)
references
References 31 publications
9
123
0
Order By: Relevance
“…Episodic synoptic perturbations, due to maritime air intrusions produce wind speeds of up to 10 m s −1 , significantly higher temperatures (up to −20 • C) and dense cloudiness (e.g. Argentini et al 2001;Genthon et al 2013). …”
Section: Site Location and Characterisationmentioning
confidence: 99%
See 1 more Smart Citation
“…Episodic synoptic perturbations, due to maritime air intrusions produce wind speeds of up to 10 m s −1 , significantly higher temperatures (up to −20 • C) and dense cloudiness (e.g. Argentini et al 2001;Genthon et al 2013). …”
Section: Site Location and Characterisationmentioning
confidence: 99%
“…The calibration procedure was the same as described in Petenko et al (2014b): based on the validity of the Obukhov-Wyngaard "z −4/3 " height dependence of C 2 T for convective conditions, we calculated the corresponding values for each range gate of the sodar profile from the sonic C 2 T measured at 3.5 m. The converting coefficients C = C 2 T (z)/(I z 2 exp(4az)) at several levels were then averaged providing the value C = (2.67 ± 0.58) × 10 −9 K m −2/3 −2 to give C 2 T values expressed in units of K m −2/3 , where is the analog-to-digital converter count. In addition, temperature and wind-velocity profiles from a 45-m tower located at a distance of approximately 1 km were available; see a description of the tower equipment in Genthon et al (2013).…”
Section: Other Measurementsmentioning
confidence: 99%
“…4). More often than not, when ∼ 100 % RH i is observed at Dome C with conventional instruments (not adapted to sample supersaturation), both models produce significant supersaturation, occasionally reaching more than 150 % (Genthon et al, 2013). The cold microphysics parameterizations differ in the two models (see Sect.…”
Section: Introductionmentioning
confidence: 98%
“…On the other hand, many reports of relative humidity with respect to ice (RH i ) on the Antarctic Plateau reach but seem to be capped at 100 % (King and Andersen, 1999). Genthon et al (2013) compare RH i observed at Dome C on the Antarctic Plateau, using conventional solid-state sensors, with results from the ECMWF (European Center for Mediumrange Weather forecasts) meteorological analyses and from the MAR (Modèle Atmosphérique Régional) meteorological model. In both models, cold microphysics parameterizations are used which, depending on local conditions, allow for supersaturations (Sect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation